Study of Electrolytic Capacitors Model Selection and Heat Sinking - HUANG Nan; SHAO Qiang; WANG Shiping (机车电传动)
The main reason of the heat was analyzed and a method to reduce the temperature rise of electrolytic capacitors was proposed. Through the analysis of the electrolytic capacitors’ internal structure, the cooling effect of common cooling methods was analyzed, and a kind of effective cooling method of electrolytic capacitor was put forward. Feasibility and effectiveness of the proposed method was validated by the prototype test.